The TP53 Codon 72 Polymorphism and Risk of Sporadic Prostate Cancer among Iranian Patients. - Farhad Babaei; Seyed Ali Ahmadi; Ramin Abiri; Farhad Rezaei; Maryam Naseri; Mahmoud Mahmoudi; Rakhshande Nategh; Talat Mokhtari Azad (Tehran University of Medical Sciences, 2014)
The TP53 gene is one of the most frequently mutated genes amongst human malignancies, particularly TP53 codon 72 polymorphism. Furthermore, an association between the TP53 codon 72 variants and prostate cancer has been reported in several studies. Although some studies have indicated an association between the TP53 Arg/Arg variant and an increased risk for prostate cancer, other studies have shown a positive correlation between the TP53 Pro/Pro genotype instead. Therefore, to clarify if this polymorphism is associated with an increased risk of prostate cancer in Iranian men, we conducted a case-control study of 40 sporadic prostate cancer patients and 80 benign prostate hyperplasia cases.The TP53 codon 72 was genotyped using an allele specific PCR.A significant association between the TP53 codon 72 genotype and prostate cancer risk was found (OR = 6.8, 95% CI = [1.8-25.1], P = 0.005). However, the results of this study did not support an association between age, the Gleason score nor TP53 genotype at codon 72 in prostate cancer patients.TP53 codon 72 polymorphism may have a great impact in the development of prostate cancer.